Handbook of School-Based Mental Health Promotion An Evidence-Informed Framework for Implementation (The Springer Series on Human Exceptionality,, 2018)
The Springer Series on Human Exceptionality Series Editors: Donald H. Saklofske and Moshe Zeidner Handbook for School-Based Mental Health Promotion An Evidence-Informed Framework for Implementation Alan W. Leschied, Donald H. Saklofske, and Gordon L. Flett, Editors This handbook provides a comprehensive overview to implementing effective evidence-based mental health promotion in schools. It addresses issues surrounding the increasing demands on school psychologists and educational and mental health professionals to support and provide improved student well-being, learning, and academic outcomes. The volume explores factors outside the traditional framework of learning that are important in maximizing educational outcomes as well as how students learn to cope with emotional challenges that confront them both during their school years and across the lifespan. Chapters offer robust examples of successful programs and interventions, addressing a range of student issues, including depression, self-harm, social anxiety, high-achiever anxiety, and hidden distress. In addition, chapters explore ways in which mental health and education professionals can implement evidence-informed programs, from the testing and experimental stages to actual use within schools and classrooms. Topics featured in this handbook include: · A Canadian perspective to mental health literacy and teacher preparation. · The relevance of emotional intelligence in the effectiveness of delivering school-based mental health programs. · Intervention programs for reducing self-stigma in children and adolescents. · School-based suicide prevention and intervention. · Mindfulness-based programs in school settings. · Implementing emotional intelligence programs in Australian schools. The Handbook for School-Based Mental Health Promotion is a must-have resource for researchers, clinicians and related professionals, and policymakers as well as graduate students across such interrelated disciplines as child and school psychology, social work, education policy and politics, special and general education, public health, school nursing, occupational therapy, psychiatry, school counseling, and family studies. .